Solar Energy Adoption in Nigerian Mosques: A Comprehensive Case Study - Muhammad Suleiman; Yusuf Sulaiman Imam; Bayero Ibrahim (Ahad: Multidisciplinary Journal of Islamic Studies, 2025)
The adoption of solar Energy in Nigeria has increased significantly due to rising energy demand, unreliable grid supply, and falling costs of renewable technologies. This paper provides an extensive analysis of the adoption of solar energy in Nigerian mosques, exploring its drivers, implementation processes, socio-economic impacts, policy considerations, and alignment with Islamic environmental ethics. Using a mixed-methods research design, the paper assesses feasibility. The research incorporates national case studies from Kano, Lagos, Zaria, and the North-East region, highlighting successes, challenges, and opportunities. Findings demonstrate that solar-powered mosques not only reduce operational costs but also serve as catalysts for community awareness of renewable energy, environmental stewardship, and sustainable development